Preliminary Study: Exploring Malaysian Parents' Views and Practices in Delivering Sexuality Education to Their Adolescents - Mohammed Rasheedan, Ellin; Siti Hazariah, Abdul Hamid; Siti Roshaidai, Mohd Arifin; Haliza, Hasan; SAJARATULNISAH, OTHMAN; NORHASMAH, MOHD ZAIN (2024)
In the rapidly evolving landscape of the modern world, the importance of comprehensive sexuality education has gained immense significance. This preliminary research aims to delve into the perspectives and practices of Malaysian parents regarding the delivery of effective sexuality education to their adolescents. To achieve this objective, a qualitative approach was adopted, involving semi-structured interviews with six exemplary parents, as identified and referred by a prominent parent-related non-governmental organization. Thematic analysis was utilized to identify significant themes, with consent duly obtained from all participants. The interviews were audio-recorded and transcribed verbatim, and the transcripts were analyzed using Atlas Ti software. Several key themes emerged from the interviews, shedding light on the multifaceted nature of sexuality education in the Malaysian context. These themes included the integration of Islamic principles as a guiding framework, the importance of age-appropriate content, the need for promoting gender affirmation, and the consideration of a suitable sexual education model. In conclusion, this preliminary research suggests that Malaysian parents exhibit a diverse range of views and practices when it comes to delivering sexuality education to their adolescents. These findings underscore the necessity of developing tailored, culturally sensitive, and inclusive approaches to sexuality education in Malaysia, where the intersection of cultural, religious, and modern values is especially pertinent. Further research and policy initiatives should focus on better understanding these dynamics and promoting open and informed discussions about sexuality education within the Malaysian family context.